The Relationship Between Pregnancy Distance And Postpartum Hemorrhage At The UPTD Lotu Health Center, North Nias Regency In 2023 - Hayati , Nila (Sean Institute, 2024)
Post partum bleeding is bleeding that exceeds 500 cc after 24 hours. Post partum hemorrhage is the main cause of maternal death. Every day in 2020 nearly 800 women died from preventable causes related to pregnancy and childbirth. One effort to prevent postpartum hemorrhage is to maintain pregnancy spacing. This study aims to determine the relationship between pregnancy distance and postpartum hemorrhage at the UPTD Lotu Community Health Center, North Nias Regency in 2023. This research is a retrospective study with a cross-sectional approach. This research was carried out from 1 September 2023 to 30 September 2023. The population was 20 people. Sampling used total sampling with a sample size of 20 people. The research results showed that the majority of maternal pregnancies in the UPTD of the Lotu Health Center, North Nias Regency were ≥2 years and the majority of postpartum bleeding in the UPTD of the Lotu Health Center, North Nias Regency was <500 ml. Based on the results of the chisquare test, the p value = 0.001 <0.05. The conclusion in this study is that there is a relationship between pregnancy distance and postpartum hemorrhage in the UPTD of the Lotu Health Center, North Nias Regency in 2023. The suggestion in this research is that the UPTD of the Lotu Health Center, North Nias Regency, carries out continuous education, especially regarding the risks that may occur if the pregnancy distance is too close, especially as it can cause postpartum hemorrhage.